Engineering PtFe/LiO2 Frontier Orbital Interaction in Li–O2 Batteries - Zhou, Yin; Yin, Kun; Zhang, Tian; Feng, Dongyu; Li, Jiapei; Zhu, Anquan; Lin, Dewu; Xue, Pan; Liu, Yu; Liu, Yongyu; Liu, Kai; Liu, Kunlun; et al. (Nano-Micro Letters, 2026)
Elucidating the structure–activity relationship between the electronic structure of catalytic active sites and oxygen evolution reaction (OER) activity at the orbital level is critical yet challenging in lithium–oxygen (Li–O2) batteries. Herein, employing frontier molecular orbital theory, we designed a Pt-based catalyst as a model cathode to investigate the influence of frontier orbital interactions between the Pt dz2 orbital and the 5σ orbital of LiO2 on the OER activity. Specifically, compared to the pure Pt catalyst, the dz2–dz2 orbital coupling between low-electronegativity Fe and Pt in PtFe catalyst induces predominant electron transfer from Fe to the dz2 frontier orbital of Pt. As the Pt content in PtFe alloys increases progressively (from Pt58Fe42, Pt67Fe33 to Pt76Fe24), the electron population of the Pt 5dz2 orbital gradually decreases (1.92 for Pt58Fe42, 1.85 for Pt67Fe33, and 1.80 for Pt76Fe24). This leads to a gradual enhancement in the strength of interactions between the Pt dz2 orbital and the frontier orbitals of LiO2, consequently resulting in a progressive decline in the OER catalytic activity. Establishing the correlating between the electron population in the dz2 frontier orbital and OER activity provides a descriptor for designing efficient electrocatalysts in Li–O2 batteries. Highlights: 1 PtFe catalyst was rationally designed based on frontier molecular orbital theory to investigate orbital-level interactions for enhanced oxygen evolution reaction activity in Li–O2 batteries. 2 The dz2–dz2 orbital coupling between Fe and Pt leads to electron donation from Fe to Pt, increasing electron population in the Pt dz2 orbital. 3 Excess electrons from the Pt dz2 orbital occupy antibonding states with LiO2, weakening interaction strength and boosting oxygen evolution reaction kinetics.